Comparison of clinical and lab profile between steroid sensitive and steroid resistant nephrotic syndrome at onset of disease and evaluating predictors for developing steroid resistance in nephrotic syndrome - Palaniyandi, Anitha; Palaniyandi, Subramani (International Journal of Contemporary Pediatrics, 2020)
Background: Nephrotic syndrome is a notable chronic disease in children. The objective of this study was to compare the clinical and lab profile between steroid sensitive nephrotic syndrome and steroid resistant nephrotic syndrome at the onset of disease. Certain parameters were tested if they could be significate predictors of developing steroid resistance at the onset of first episode of nephrotic syndrome. Methods: Retrospective observation study done children 1-12 years diagnosed with nephrotic syndrome in Sri Ramachandra Medical College and Hospital, Department of Paediatrics, Chennai. Sample size 150. Period of study Jan 2013- Dec 2015. Variables considered were age at onset, sex, parental consanguinity with essential lab parameters done at the onset of nephrotic syndrome proteinuria, pyuria, microscopic hematuria, urine protein creatinine ratio, serum creatinine, serum triglycerides and serum albumin. Children less than 1 year of age, cases with secondary causes of nephrotic syndrome and steroid dependant nephrotic syndrome, children with incomplete records were not included in this study. 150 cases who fulfilled the study criteria were included in this study. Results: 75 cases of steroid sensitive nephrotic syndrome (SSNS) were compared with an equal number of steroid resistant nephrotic syndrome (SRNS). 85 children had onset of disease before 3 years of age and majority had 3+ proteinuria and males predominated in both the groups. The overall consanguinity rates were higher among SRNS group. Triglyceride level >300 mg/dl predominated in SRNS group along with a higher severity of hypoalbuminemia when compared to SSNS group. None of the parameters tested were significant predictors of developing SRNS subsequently. Conclusions: Comparing steroid sensitive with steroid resistance nephrotic syndrome, no lab parameter could identify the risk of a child developing steroid resistance subsequently. This could be a field of interest in future studies that could predict the development of steroid resistance at the onset of first episode of nephrotic syndrome itself.